Dynamics of the status of groundwater in the Polish Lowland: the River Gwda catchment example - Jamorska, Izabela; Kubiak-Wójcicka, Katarzyna; Krawiec, Arkadiusz (Geologos, 2019)
The aim of the present study is to monitor changes in the location of the groundwater table in the catchment area of the River Gwda within the Quaternary and Neogene water-bearing level over a 35-year period, between 1981 and 2015. In addition, on account of very diverse total annual precipitation levels in particular parts of the catchment, attempts were made to determine the influence of precipitation on the location of the groundwater table. By correlating groundwater level and meteorological parameters (precipitation), it was discovered that precipitation in the previous year made the largest impact on the groundwater table. Moreover, low precipitation totals in the southern part of the catchment are not discernible in groundwater table fluctuations, which is linked to the location of the observation well within the drainage zone as well as to water ascension from deeper aquifers.